Iridoides, triterpenos e outros constituintes das cascas do caule e flores de Tabebuia caraiba Bignoniaceae - Aloízio de O. Soares; Caroline Tieppo; Luzinátia Ramos Soares; Joaquim Corsino; Alex Fonseca Souza; Fernanda R. Garcez; Walmir S. Garcez (Química Nova)
The trunk bark of Tabebuia caraiba Bignoniaceae was found to contain four novel iridoids, 6-O-E-p-coumaroyljioglutin D (2), 6-O-E-p-coumaroyl-3-demethyl-3-O-ethyljioglutin D (3), 6-O-E-p-coumaroyl-1-demethyl-1-O-ethyljioglutin D (4), 7-O-E-p-coumaroyljiofuranaldehyde (5), three known iridoids, including one iridoid glucoside, jioglutin D (1), rehmaglutin D (6), 6-O-E-p-coumaroylcatalpol (7). From the flowers were obtained six triterpenes, betulinic acid (8), olean-12-en-3-one (9), β-amyrin (10), oleanolic acid (11), ursolic acid (12), 3-O-E-p-coumaroylursolic acid (13), 2α-hydroxyursolic acid (14), 6β,19α-dihydroxyursolic acid (15), and one phenylethanoid, tyrosol (16), in addition to β-sitosterol, β-sitosterol-3-O-β-D-glucopyranoside and β-sitosterol-3-O-β-D-(6´-O-acyl)-glucopyranoside and E-p-coumaric acid. The structures of the isolated compounds were established on the basis of 1D and 2D NMR spectroscopic techniques. The chemical profile of the trunk bark of the plant was determined by HPLC/DAD/HRESIMS and did not present a good correlation with the phytochemical study. It did not detect most of the isolated substances and allowed to propose the presence of some non-isolated compounds.